The Impact of Socioeconomic Status on Outcomes in Orthopaedic Surgery. (4th March 2020) - Li, Xinning; Galvin, Joseph W.; Li, Chris; Agrawal, Ravi; Curry, Emily J.
Abstract : Social determinants of health is considered an umbrella term that includes factors such as education level, income and occupation, social class, social status, race, ethnicity, and sex. Socioeconomic status (SES) is a fundamental cause of health-care disparities and is a critical issue affecting all fields of medicine. In orthopaedic surgery, the quality of care provided, whether by surgical intervention or nonoperative treatment, is closely intertwined with social factors related to the SES of a patient. SES is a known predictor of morbidity and mortality within different orthopaedic subspecialties, and modifiable factors contributing to low SES must be evaluated and optimized to reduce health-care disparities. With the emergence of value-based health care and solutions seeking to improve outcomes and reduce cost, progress is being made toward reducing negative surgical outcome predictors associated with SES. With the transition from fee-for-service models to alternate payment models based on practice-specific quality data, identification and risk adjustment based on SES variables will be critical to prevent patient exclusion, delay in care, and misrepresentation of a surgeon's relative performance based on patient-reported outcomes.